Warung Kopi: Bursa Informasi Masyarakat Aceh (Analisis Teori Difusi Inovasi dan Two Step Flow) - AG , Hamdani (At-Tabayyuun: Journal Islamic Studies, 2019)
In Achenes, the coffee shop has an important role –not merely "cultural products" symbol of collective orientation that is deeply entrenched in society, but rather as an instrument transactions (exchange) information, which has undergone a process of evolution and innovation dynamic and heritage regeneration. There adage in Aceh, that the coffee shop is synonymous with "street", so that the term "coffee shops news, politics sidewalk, coffee shop business," and so forth which implies the impression of "cheap". But, that was then, when the coffee shop still faced "burnt", identical to the unemployed, a mystic fan tail, village thugs, cang arrows and Peh tem (windbag). Meanwhile, a coffee shop which has now evolved into a cafe, everything is completely up todate with the current condition paced and modern wah. In addition, transaction centers (exchanges) information locally, regionally and globally, the coffee shop has now become the arena of the business meeting, politicians, professional, well kongkow kongkow event fellow lectures, business partners, youth